Exploring Pre-service English Teachers’ Self-Efficacy in the Practice of Online English Classroom - Nito Majid Mujtahid; Ngadiso Ngadiso; Slamet Supriyadi (STAI Hubbulwathan Duri, 2023)
This study focused on the concerns regarding pre-service teachers' experience of how to integrate technology into classroom teaching and the appropriate approaches to apply educational technologies for their students in the online classroom. The qualitative case study was used to get an in-depth analysis of pre-service teachers’ self-efficacy. Moreover, this study used the self-efficacy theory proposed by Bandura to explore pre-service teachers’ self-efficacy when using technology on purpose to teach in online ways. There were 10 participants from the private university in Indonesia with the English education department as their major. The data were collected in the form of observation, written interviews and in-depth interviews. The study revealed that there are some factors that would increase pre-service teachers' self-efficacy including their experience with technology, such as observing role models, social persuasion toward integrating technology, and physiological and emotional states of the pre-service teacher. However, the number of individuals and the area included in this study limit the scope of this investigation. As a result, more research is likely to address a broader range of topics, as well as viewpoints from in-service teachers.